Bioprocess designing towards clean energy production from industrial wastewater - Krishnan, Santhana; Mohd, Nasrullah; Saravanan, Prabhu; Mohd Fadhil, Md Din (Frontiers Media SA, 2024)
Bioprocess designing towards clean energy production from industrial wastewater